2018
DOI: 10.4236/ojbm.2018.62018
|View full text |Cite
|
Sign up to set email alerts
|

Research on Perceptions of Organizational Politics and Its Influence on Employee Silence

Abstract: Perceptions of Organizational Politics and employee silence, as two topics to be avoided in organizations, have long drawn widespread attention in the field of organizational behavior and human resources. Based on the theory of social exchange and the theory of individual-organization fit, this paper aims to explore the relationship between the Perceptions of Organizational Politics and employee silence, as well as the Regulatory effect of Conscientiousness and organizational identification. Firstly, it define… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 21 publications
0
11
0
1
Order By: Relevance
“…This study also confirmed the significant direct impact of POP on WO, which is in alignment with the arguments of social exchange theory. Perceiving high level of organizational politics tends to destroy interpersonal exchange relationships ( Sun and Xia, 2018 ), leading to an increased sense of WO among the organizational members ( Scott et al., 2013 ). From the results of this study, ID appeared as a significant intervening variable in the relationship between POP and WO.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This study also confirmed the significant direct impact of POP on WO, which is in alignment with the arguments of social exchange theory. Perceiving high level of organizational politics tends to destroy interpersonal exchange relationships ( Sun and Xia, 2018 ), leading to an increased sense of WO among the organizational members ( Scott et al., 2013 ). From the results of this study, ID appeared as a significant intervening variable in the relationship between POP and WO.…”
Section: Discussionmentioning
confidence: 99%
“…In general, an increased perception of organizational politics can cause employees' feelings of unfairness, powerlessness, anxiety, increased awareness of self-protection, imbalanced interpersonal relationship, destruction of the exchange relationship between the employees, triggering the sense of separation and crowding out by colleagues (Sun and Xia, 2018).…”
Section: Perceived Organizational Politics and Workplace Ostracismmentioning
confidence: 99%
See 2 more Smart Citations
“…In other studies, conducted with teachers working in different educational levels, it was found that organisational silence was low (Demirtas & Kucuk, 2019;Demirtas & Nacar, 2018;Kalay, Ograk, Bal & Nisanci, 2014;Kiranli Gungor & Potuk, 2018;Yildirim & Carikci, 2017). Fatima, Salah-Ud-Din, Khan, Hassan & Hoti (2015), researchers working on organisational silence in various sectors, stated that employees had a high level of organisational silence; Turgut and Akbolat (2017) and Sun and Xia (2018) indicated a medium level of organisational silence.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%